The Role Of Artificial Intelligence In Fostering Ethical Business Practices: A Qualitative Study On Digital Marketing Advancements In Indonesia - Muhammad Rizal; Eri Kusnanto; Farah Qalbia; Benardi Benardi (Proceeding of The International Conference on Business and Economics, 2023)
This qualitative inquiry aims to explore the impact of Artificial Intelligence (AI) on promoting ethical business practices within the realm of digital marketing in Indonesia. The research model adopts a qualitative approach, utilizing semi-structured interviews with key stakeholders in the digital marketing sector. Sampling techniques involve purposive sampling to ensure representation from various sectors such as industry professionals, policymakers, and consumer advocacy groups. Data analysis employs thematic analysis, allowing for the identification of recurring themes and patterns related to the integration of AI in digital marketing practices and its influence on ethical considerations. Preliminary findings suggest that AI implementation in digital marketing facilitates transparency, personalization, and accountability, thereby fostering ethical practices among businesses operating in Indonesia's digital landscape. This study contributes to the ongoing discourse on the ethical implications of AI adoption in emerging markets, providing insights for policymakers and industry stakeholders to develop frameworks that promote responsible AI use in business operations.